English Teachers’ Beliefs about Active Learning and Classroom Practices in Secondary Schools: The Case of Grades 11 and 12 in North Shoa Zone (Salale), Oromia - Mulugeta Addisu Hararu; Regassa, Taye (LET: Linguistics, Literature and English Teaching Journal, 2025)
The study aimed to investigate secondary school EFL teachers’ beliefs about active learning and classroom practices in North Shoa of the Oromia Regional State. The researcher used a mixed-method technique to collect the relevant data. The study used a simple random sampling technique to select the schools. Data were collected from 72 EFL teachers who teach in grades 11 and 12 in 15 government schools using census/complete enumeration and purposive sampling techniques. The data were collected via questionnaire, interview, and classroom observation. Then, the data were analyzed both quantitatively by using descriptive statistical tools such as mean and standard deviation and qualitatively through descriptive with brief reports following a grounded theory model and teacher’s instructional patterns and students’ behaviors. The findings from the questionnaire and interview revealed that teachers hold strong positive beliefs regarding the contribution of implementing active learning for the students’ learning. Conversely, the results from classroom observation data indicated that teachers predominantly use a teacher-centered approach. This discrepancy is attributed to constraints such as teachers in favor of teacher-centered practice, students’ poor background, and lack of support from stakeholders. These factors hinder the effective implementation of innovative teaching strategies. Therefore, to solve these challenges, increasing collaboration among teachers, educators, and stakeholders is important.